The Engagement of Cytochrome P450 Enzymes in Tryptophan Metabolism - Anna Haduch; Ewa Bromek; Wojciech Kuban; Władysława Anna Daniel (Metabolites, 2023)
Tryptophan is metabolized along three main metabolic pathways, namely the kynurenine, serotonin and indole pathways. The majority of tryptophan is transformed via the kynurenine pathway, catalyzed by tryptophan-2,3-dioxygenase or indoleamine-2,3-dioxygenase, leading to neuroprotective kynurenic acid or neurotoxic quinolinic acid. Serotonin synthesized by tryptophan hydroxylase, and aromatic L-amino acid decarboxylase enters the metabolic cycle: serotonin → N-acetylserotonin → melatonin → 5-methoxytryptamine→serotonin. Recent studies indicate that serotonin can also be synthesized by cytochrome P450 (CYP), via the CYP2D6-mediated 5-methoxytryptamine O-demethylation, while melatonin is catabolized by CYP1A2, CYP1A1 and CYP1B1 via aromatic 6-hydroxylation and by CYP2C19 and CYP1A2 via O-demethylation. In gut microbes, tryptophan is metabolized to indole and indole derivatives. Some of those metabolites act as activators or inhibitors of the aryl hydrocarbon receptor, thus regulating the expression of CYP1 family enzymes, xenobiotic metabolism and tumorigenesis. The indole formed in this way is further oxidized to indoxyl and indigoid pigments by CYP2A6, CYP2C19 and CYP2E1. The products of gut-microbial tryptophan metabolism can also inhibit the steroid-hormone-synthesizing CYP11A1. In plants, CYP79B2 and CYP79B3 were found to catalyze N-hydroxylation of tryptophan to form indole-3-acetaldoxime while CYP83B1 was reported to form indole-3-acetaldoxime N-oxide in the biosynthetic pathway of indole glucosinolates, considered to be defense compounds and intermediates in the biosynthesis of phytohormones. Thus, cytochrome P450 is engaged in the metabolism of tryptophan and its indole derivatives in humans, animals, plants and microbes, producing biologically active metabolites which exert positive or negative actions on living organisms. Some tryptophan-derived metabolites may influence cytochrome P450 expression, affecting cellular homeostasis and xenobiotic metabolism.